TPACK Capabilities of Mathematics Teachers: An Overview Based on Teacher Certification Status and School Accreditation - Busnawir Busnawir; Mery Aryanti; Nana Sumarna; Kodirun Kodirun; Hafiludin Samparadja (Institut Pendidikan Indonesia Garut, 2023)
Keterampilan TPACK guru dapat dipengaruhi oleh status sertifikasi guru dan akreditasi sekolah. Guru bersertifikat diharapkan mampu mengintegrasikan TPACK dengan baik dalam pembelajaran. Tujuan penelitian ini untuk mengkaji kemampuan TPACK guru matematika sekolah menengah berdasarkan status sertifikasi guru dan akreditasi sekolah di Kabupaten Buton Utara. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan metode survey. Populasi penelitian sebanyak 53 guru matematika sekaligus sebagai subyek penelitian. Data dikumpulkan melalui angket, observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa kemampuan penguasaan TPACK guru matematika sekolah menengah di Kabupaten Buton Utara termasuk kategori rendah; ada perbedaan kemampuan TPACK yang signifikan antara guru matematika di sekolah terakreditasi A dan B; terdapat perbedaan yang signifikan keterampilan TPACK antara guru matematika di sekolah terakreditasi A dan C; tidak terdapat perbedaan kemampuan TPACK antara guru matematika di sekolah terakreditasi B dan C; terdapat perbedaan yang signifikan kemampuan TPACK antara guru bersertifikasi dan tidak bersertifikasi di sekolah terakreditasi B; tidak ada perbedaan keterampilan TPACK antara guru bersertifikasi dan tidak bersertifikasi di sekolah terakreditasi A dan C.Teachers' TPACK skills can be influenced by teacher certification status and school accreditation. Certified teachers are expected to be able to integrate TPACK well in learning. The purpose of this study was to examine the TPACK ability of high school mathematics teachers based on teacher certification status and school accreditation in North Buton District. This research uses a quantitative descriptive approach with a survey method. The research population consisted of 53 mathematics teachers who were also research subjects. Data were collected through questionnaires, observations, interviews, and documentation. The results showed that the TPACK mastery ability of high school mathematics teachers in North Buton Regency was in a low category; there is a significant difference in TPACK ability between mathematics teachers in schools accredited A and B; there is a significant difference in TPACK skills between mathematics teachers in schools accredited A and C; there is no difference in TPACK abilities between mathematics teachers in schools accredited B and C; there is a significant difference in the ability of TPACK between certified and uncertified teachers in schools accredited B; there is no difference in TPACK skills between certified and uncertified teachers in schools accredited A and C.